Humidity self-powered component and preparation method thereof
Patent Information
- Application Number
- CN202611199807.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
然而,由于放电性能不稳定以及缺乏与放电相关的工作机制,将外界湿度环境转化为柔性器件足够稳定的电力输出依旧是巨大的挑战
[0018]本发明提供的湿度自供电元器件可以在除了相对湿度为0的任何湿度情况下工作(即环境的相对湿度RH:0<RH≤100 %)。在相对湿度RH = 80%的情况下,自供电元器件可以实现的有效电压密度在0.3~0.5 V/cm2之间,最高有效电流密度可达1100 μA/cm2,平均有效电流密度可在10~100 μA/cm2之间,其功率密度可达到10~50μW/cm2。通过串联,并联等连接方式,本发明湿度自供电元器件可以稳定实现1.5V以上,1A以上的性能,满足常规小型化用电设备的基本需求。相比于传统的电池系统,本发明湿度自供电元器件主要为二维材料构成,能量密度高,质地轻盈,且无需充电,能够在低载荷情况下通过串并联的方式满足小型轻质用电器的电能供应,亦可通过自身电压电流性能配合其他电源对电路进行调制,实现稳定电能输出。此外,本发明提供的湿度自供电元器件具有柔性特性,在可穿戴设备等柔性软体设备中具有极高的应用价值,有望替代柔性软体设备中的电池设备,减少刚性电池结构对柔性设备的影响。
Smart Images

Figure CN122993503A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of humidity self-powered technology, specifically to a humidity self-powered component and its preparation method. Background Technology
[0002] In recent years, with the gradual expansion of application scenarios for flexible machinery and equipment, energy supply equipment capable of adapting to desolate and humid water network systems has become a key focus of pre-research. Compared with other self-powered technologies such as triboelectric and piezoelectric power generation developed in recent years, humidity self-powered power generation can obtain moisture from the humid atmosphere and ensure continuous energy input, showing broad application prospects in cutting-edge application scenarios such as wearable devices and other flexible soft devices. However, due to unstable discharge performance and the lack of a discharge-related working mechanism, converting the external humidity environment into a sufficiently stable power output for flexible devices remains a significant challenge.
[0003] Currently, publicly available design cases of humidity self-powered components are mainly conceptual and experimental. Existing technologies disclose methods and devices for generating electricity from moisture, but these devices need to be carried out in humid air with high water vapor content. They only have good power generation effect under conditions where the relative humidity is 100% or higher and water molecules are saturated. Their practical application scenarios are very limited. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a humidity-self-powered component and its preparation method. The humidity-self-powered component provided by this invention does not require charging and can generate electricity by collecting external humidity, thus realizing the collection and release of electrical energy.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides a humidity-controlled self-powered device, comprising a multilayer modified polybenzimidazole layer with a gradient ion concentration, a porous hydrophilic graphene electrode located on one side of the multilayer modified polybenzimidazole layer, and a counter electrode located on the other side of the multilayer modified polybenzimidazole layer. The modified polybenzimidazole includes acid-modified polybenzimidazole, or includes both acid-modified and alkali-modified polybenzimidazole. When it is acid-modified polybenzimidazole, the ion is a hydrogen ion; when it is alkali-modified polybenzimidazole, the ion is a hydroxide ion. The porous hydrophilic graphene electrode is disposed on one side of the acid-modified polybenzimidazole layer.
[0006] Preferably, the multilayer modified polybenzimidazole layer with gradient ion concentration is a multilayer modified polybenzimidazole layer with a single ion concentration gradient or a multilayer modified polybenzimidazole layer with two ion concentration gradients. The multilayer modified polybenzimidazole layer with a single ion concentration gradient is a multilayer acid-modified polybenzimidazole layer stacked together, in which the hydrogen ion concentration decreases sequentially from top to bottom; the porous hydrophilic graphene electrode is disposed on the side with high hydrogen ion concentration. The multilayer modified polybenzimidazole layer with two ion concentration gradients includes an acid-modified polybenzimidazole layer at the top and an alkali-modified polybenzimidazole layer at the bottom. The acid-modified polybenzimidazole layer has one or more layers, and when it has multiple layers, the hydrogen ion concentration decreases from top to bottom. The alkali-modified polybenzimidazole layer has one or more layers, and when it has multiple layers, the hydroxide ion concentration increases from top to bottom.
[0007] Preferably, the thickness of the monolayer modified polybenzimidazole layer is independently selected from 5 to 100 μm; The number of layers in the multilayer modified polybenzimidazole layer is 2 to 10.
[0008] Preferably, the thickness of the porous hydrophilic graphene electrode is 50~1000 μm; The counter electrode includes one of graphene electrode, carbon nanomaterial electrode and metal electrode, and the thickness of the counter electrode is 50~1000 μm.
[0009] Preferably, the humidity self-powered component is used alone or in series or parallel.
[0010] This invention provides a method for preparing the above-mentioned humidity-self-powered component, comprising the following steps: Multiple modified polybenzimidazole membranes with different ion concentrations are provided. Multiple acid-modified polybenzimidazole layers are stacked in order of hydrogen ion concentration from high to low, or acid-modified polybenzimidazole layers and alkali-modified polybenzimidazole layers are stacked in order of hydrogen ion concentration from high to low and hydroxide ion concentration from low to high, to obtain a multilayer modified polybenzimidazole layer with gradient ion concentration. The multilayer modified polybenzimidazole layer with gradient ion concentration is hot-pressed to obtain a hot-pressed material; A porous hydrophilic graphene electrode is fabricated on one side of the hot-pressed material with a high hydrogen ion concentration, and a counter electrode is set on the other side to obtain a humidity-self-powered component.
[0011] A preferred method for preparing modified polybenzimidazole membranes with different ion concentrations includes the following steps: Multiple polybenzimidazole membranes were immersed in acidic or alkaline solutions of different concentrations to perform acid modification or alkali modification, resulting in modified polybenzimidazole membranes with different ion concentrations. The acidic solution includes phosphoric acid solution, sulfuric acid solution, nitric acid solution or hydrochloric acid solution; The alkaline solution includes sodium hydroxide solution and / or potassium hydroxide solution; The concentration of the acidic or alkaline solution is selected from 0 to 100% saturation concentration, and the acid modification or alkaline modification time is independently 24 to 48 hours.
[0012] Preferably, the method for preparing the porous hydrophilic graphene electrode includes the following steps: A porous hydrophilic graphene electrode is obtained on the surface of the hot-pressed material by laser irradiation. The parameters for the laser irradiation include: the laser is a carbon dioxide laser, the wavelength is 10.6 μm, and the wavenumber is 900~1500 cm⁻¹. -1 The irradiation power is 0.5~10W, the laser irradiation scanning speed is 1~12 inch / s, the laser irradiation image density is 200~1000 PPI, and the defocusing degree is 0~2cm.
[0013] Preferably, the method for setting the counter electrode includes the following steps: When the counter electrode is a porous hydrophilic graphene electrode, the other side of the hot-pressed material is irradiated with a laser to obtain porous hydrophilic graphene as the counter electrode. When the counter electrode is a carbon nanomaterial electrode or a metal electrode, the counter electrode and a multilayer modified polybenzimidazole layer with a gradient ion concentration are simultaneously hot-pressed.
[0014] This invention provides the application of the above-mentioned humidity self-powered components in humidity power generation.
[0015] This invention provides a humidity-controlled self-powered device, comprising a multilayer modified polybenzimidazole layer with a gradient ion concentration, a porous hygroscopic graphene electrode, and a counter electrode. This invention utilizes the hygroscopic properties of polybenzimidazole material to create an internal ion (hydrogen ion and / or hydroxide ion) concentration gradient. With the aid of water and the internal ion concentration difference, charge transfer occurs within the material, generating an internal electric field. The external circuit is then powered via the connected graphene electrode and counter electrode. This process is spontaneous under humid conditions, exhibiting self-generating power.
[0016] This invention develops a multilayer modified polybenzimidazole layer with hygroscopic properties. This material has a significant ion concentration gradient within it (which can be called an ion concentration gradient composite material, or simply gradient composite). This invention absorbs moisture through the multilayer modified polybenzimidazole layer. The moisture binds to the polymer framework of the polybenzimidazole material, providing pathways for ion migration within the gradient composite, thereby achieving stable migration of charged ions. The electric field generated by this ion migration is compensated by an external circuit, thus drawing an external circuit current, achieving the main purpose of self-powered moisture absorption. In addition, the graphene electrode, laser-induced fabricated directly on the surface of the multilayer modified polybenzimidazole layer, not only has conductivity but also the ability to capture moisture, further promoting the moisture absorption of the gradient composite. The main function of the counter electrode is to connect to the external circuit; together with the graphene electrode, it can be connected to the external circuit to achieve a stable power supply.
[0017] Furthermore, the multilayer modified polybenzimidazole layer with gradient ion concentrations of the present invention includes a multilayer modified polybenzimidazole layer with a single ion concentration gradient or a multilayer modified polybenzimidazole layer with two ion concentration gradients. The single ion concentration gradient is constructed using multilayer acid-modified polybenzimidazole materials, and the proton (i.e., hydrogen ion) is the only ion transported by the single ion concentration gradient. The present invention can design and prepare hydrogen ion concentration gradient composites by combining two or more polybenzimidazole film materials treated with different acid solutions. The multilayer modified polybenzimidazole layer with two ion concentration gradients includes an upper acid-modified polybenzimidazole layer and a lower alkali-modified polybenzimidazole layer. By combining the two materials in a concentration-varying manner, a concentration gradient composite material in which hydrogen ions and hydroxide ions coexist can be prepared. Under the action of water absorption, single gradient composites use the concentration difference as the driving force and the absorbed water molecules as the ion transport path to realize the migration of ions inside the gradient composites; gradient composites with two types of ions use the concentration gradient of hydrogen ions and hydroxide ions at their relative positions and the binding effect of hydrogen ions and hydroxide ions to form water molecules to further attract water molecules, promote ion migration, and realize the migration of ions inside the gradient composites.
[0018] The humidity-controlled self-powered component provided by this invention can operate under any humidity condition except for a relative humidity of 0% (i.e., ambient relative humidity RH: 0 < RH ≤ 100%). At a relative humidity of RH = 80%, the self-powered component can achieve an effective voltage density of 0.3~0.5 V / cm². 2 Between these values, the highest effective current density can reach 1100 μA / cm. 2 The average effective current density can be 10~100 μA / cm 2 Its power density can reach 10~50μW / cm². 2Through series and parallel connections, the humidity-controlled self-powered component of this invention can stably achieve performance above 1.5V and 1A, meeting the basic requirements of conventional miniaturized electrical devices. Compared to traditional battery systems, the humidity-controlled self-powered component of this invention is mainly composed of two-dimensional materials, has high energy density, is lightweight, and requires no charging. It can supply power to small, lightweight electrical appliances under low load conditions through series and parallel connections. It can also modulate the circuit using its own voltage and current performance in conjunction with other power sources to achieve stable power output. Furthermore, the humidity-controlled self-powered component provided by this invention has flexible characteristics, making it highly valuable for applications in flexible soft devices such as wearable devices. It is expected to replace battery devices in flexible soft devices, reducing the impact of rigid battery structures on flexible devices. Attached Figure Description
[0019] Figure 1 The diagrams show the configuration designs of composites with a single ion concentration gradient and composites with two ion concentration gradients. Figure 2 This is a flowchart illustrating the fabrication process of the humidity-self-powered component of the present invention. Figure 3 The peak voltage of the humidity self-powered component under different concentration gradients; Figure 4 The peak current of the humidity self-powered component under different concentration gradients; Figure 5 The average voltage and average current of the humidity self-powered components under different concentration gradients; Figure 6 This is a graph showing the change in electrical power under varying load conditions. Figure 7 The average voltage and average current of the humidity self-powered components under different concentration gradients; Figure 8 The results show the performance comparison of different counter electrodes in Examples 4 and 7; Figure 9 It is a series connection of 12 self-powered components with single ion concentration gradient humidity; Figure 10 The long-term supply voltage condition for a 12-unit series device; Figure 11 Humidity monitoring results for self-powered humidity components; Figure 12 This is a comparison chart of voltage and current performance between products without and with gradient composite materials. Figure 13 This is a performance comparison between the hygroscopic electrode and the unmodified hydrophobic electrode. Detailed Implementation
[0020] In this invention, the terms "upper" and "lower" refer to relative orientations. In practical applications, if the overall structure undergoes spatial rotation, the relative relationship between the two will change accordingly, and both will fall within the scope of protection of this invention.
[0021] The present invention provides a humidity-controlled self-powered device, comprising a multilayer modified polybenzimidazole layer with a gradient ion concentration, a porous hydrophilic graphene electrode located on one side of the multilayer modified polybenzimidazole layer, and a counter electrode located on the other side of the multilayer modified polybenzimidazole layer. The modified polybenzimidazole includes acid-modified polybenzimidazole and / or alkali-modified polybenzimidazole. When it is acid-modified polybenzimidazole, the ion is a hydrogen ion; when it is alkali-modified polybenzimidazole, the ion is a hydroxide ion. The porous hydrophilic graphene electrode is disposed on one side of the acid-modified polybenzimidazole layer.
[0022] In this invention, the thickness of the single-layer modified polybenzimidazole layer is independently selected from 5 to 100 μm, more preferably 20 to 80 μm, specifically 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, and the thickness of each layer can be the same or different; the number of layers of the multilayer modified polybenzimidazole layer is preferably 2 to 10 layers, specifically 2 layers, 3 layers, 5 layers, 8 layers or 10 layers.
[0023] In this invention, the multilayer modified polybenzimidazole layer with gradient ion concentration includes a multilayer modified polybenzimidazole layer with a single ion concentration gradient or a multilayer modified polybenzimidazole layer with two ion concentration gradients. The multilayer modified polybenzimidazole layer with a single ion concentration gradient is a stacked multilayer acid-modified polybenzimidazole layer, in which the hydrogen ion concentration decreases sequentially from top to bottom. The number of layers in the multilayer modified polybenzimidazole layer with a single ion concentration gradient is preferably 2 to 10, more preferably 3 to 5. In this invention, when the multilayer modified polybenzimidazole layer has a single ion concentration gradient, the porous hydrophilic graphene electrode is disposed on the side with a high hydrogen ion concentration.
[0024] In this invention, the multilayer modified polybenzimidazole layer with two ion concentration gradients includes an upper acid-modified polybenzimidazole layer and a lower alkali-modified polybenzimidazole layer. The acid-modified polybenzimidazole layer has one or more layers, specifically 2 to 5 layers. When it is multilayered, the hydrogen ion concentration in each layer decreases sequentially from top to bottom. The alkali-modified polybenzimidazole layer has one or more layers, specifically 2 to 5 layers. When it is multilayered, the hydroxide ion concentration in each layer increases sequentially from top to bottom. In this invention, when the multilayer modified polybenzimidazole layer has two ion concentration gradients, the porous hydrophilic graphene electrode is disposed on one side of the acid-modified polybenzimidazole layer; when the acid-modified polybenzimidazole layer is multilayered, the porous hydrophilic graphene electrode is disposed on the side with a high hydrogen ion concentration.
[0025] In this invention, the thickness of the porous hydrophilic graphene electrode is preferably 50~1000 μm, more preferably 100~500 μm; the surface roughness of the porous hydrophilic graphene electrode is preferably ≤4 μm, the pore size is preferably 50 nm~5 μm, more preferably 200 nm~1 μm, and the specific surface area is preferably ≥340 m². 2 / g. In this invention, the porous graphene with a roughness of less than 4 μm exhibits hydrophilic and hygroscopic properties, which can promote the absorption of moisture on the surface of the porous graphene material. In this invention, the porous hydrophilic graphene electrode is preferably disposed on the surface of an acid-modified polybenzimidazole layer, in an acidic solution mainly composed of phosphoric acid and sulfuric acid, with an infrared spectral wavenumber of 900~1500 cm⁻¹. -1 The graphene exhibits an absorption peak, enabling acidic molecules to absorb laser energy. Acid modification primarily using phosphoric acid and sulfuric acid allows residual acid molecules in the polybenzimidazole to better absorb laser energy, forming numerous free radicals. The gas generated by these free radicals ultimately remains within the graphene layer, forming porous graphene. Due to the significant participation of phosphoric acid and sulfuric acid in the laser-induced photochemical reaction, the processed graphene possesses abundant PO, SO, PH, and SH bonds, forming hydrogen bonds with water molecules and creating an effective chemical structure for water absorption.
[0026] In this invention, the counter electrode preferably comprises one of a graphene electrode, a carbon nanomaterial electrode, and a metal electrode. The carbon nanomaterial electrode preferably comprises one or more of carbon nanotubes, reduced graphene oxide, and carbon felt. The metal electrode preferably comprises one or more of copper, nickel, and silver. Copper and nickel electrodes, due to their good adhesion and low work function, can achieve higher power generation efficiency in humidity-controlled power supply devices. In this invention, the thickness of the counter electrode is preferably 50-1000 μm, more preferably 100-500 μm.
[0027] In this invention, the self-powered humidity control components are used individually, in series, or in parallel. When connected in series, the number of self-powered humidity control components connected is preferably ≥2, more preferably 2 to 20. When connected in parallel, the number of self-powered humidity control components connected is preferably ≥2, more preferably 2 to 20.
[0028] This invention provides a method for preparing the above-mentioned humidity-self-powered component, comprising the following steps: Multiple modified polybenzimidazole membranes with different ion concentrations are provided. Multiple acid-modified polybenzimidazole layers are stacked in order of hydrogen ion concentration from high to low, or acid-modified polybenzimidazole layers and alkali-modified polybenzimidazole layers are stacked in order of hydrogen ion concentration from high to low and hydroxide ion concentration from low to high, to obtain a multilayer modified polybenzimidazole layer with gradient ion concentration. The multilayer modified polybenzimidazole layer with gradient ion concentration is hot-pressed to obtain a hot-pressed material; A porous hydrophilic graphene electrode is fabricated on one side of the hot-pressed material with a high hydrogen ion concentration, and a counter electrode is set on the other side to obtain a humidity-self-powered component.
[0029] In this invention, the method for preparing modified polybenzimidazole membranes with different ion concentrations includes the following steps: Multiple polybenzimidazole membranes were immersed in acidic or alkaline solutions of different concentrations to perform acid or alkali modification, resulting in modified polybenzimidazole membranes with different ion concentrations.
[0030] In this invention, the thickness of the polybenzimidazole film is preferably 5-100 μm, more preferably 20-80 μm. The thickness of each polybenzimidazole film can be the same or different. This invention does not have special requirements regarding the source of the polybenzimidazole film; commercially available polybenzimidazole film or self-prepared film can be used. When self-prepared, the preparation method preferably includes the following steps: Polybenzimidazole powder is mixed with an organic solvent and heated to dissolve, thus obtaining a polybenzimidazole solution. The polybenzimidazole solution was coated onto a substrate, the organic solvent was evaporated, and the substrate was peeled off after cooling to obtain a polybenzimidazole film.
[0031] In this invention, there are no special requirements for the particle size or molecular weight of the polybenzimidazole powder; commercially available polybenzimidazole powder that can ensure smooth dissolution and film formation is sufficient. In this invention, the organic solvent is preferably one or more of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP). The mass concentration of polybenzimidazole in the polybenzimidazole solution is preferably 1-10%, more preferably 2-8%. In this invention, the heating and mixing temperature is preferably 50-120°C, more preferably 60-100°C, and the time is preferably 2-7 hours, more preferably 4-5 hours. In this invention, the volatile organic solvent is preferably volatilized under normal pressure, the temperature is preferably 60-120°C, more preferably 80-100°C, and the time is preferably 6-26 hours, more preferably 12-24 hours.
[0032] In this invention, the acidic solution preferably includes a phosphoric acid solution, a sulfuric acid solution, a nitric acid solution, or a hydrochloric acid solution. In this invention, the concentration of the acidic solution is selected from 0 to 100% saturation concentration. Specifically, the concentration of the phosphoric acid solution is 0 to 85 wt% (0 wt% means no acid modification treatment, the same below), specifically 0, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, or 85 wt%; the concentration of the sulfuric acid solution is 0 to 98 wt%, specifically 0, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, 90 wt%, or 98 wt%; the concentration of the hydrochloric acid solution is 0 to 37 wt%, specifically 0, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, or 37 wt%; the concentration of the nitric acid solution is 0 to 30 wt%. The wt% can be 0, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, or 30 wt%. In this invention, the concentration of the acidic solution needs to be selected according to the number of modified membranes to ensure that the modified concentration of each membrane is different.
[0033] In this invention, the alkaline solution includes sodium hydroxide solution and / or potassium hydroxide solution; the concentration of the alkaline solution is selected from 0 to 100% saturation concentration. Specifically, the concentration of potassium hydroxide solution is 0 to 10 mol / L (0 M means no alkali modification treatment, the same below), specifically 0, 1 mol / L, 2 mol / L, 5 mol / L, 8 mol / L or 10 mol / L; the concentration of sodium hydroxide is 0 to 5.5 mol / L, specifically 0, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or 5.5 mol / L.
[0034] In this invention, the acid-modification or alkali-modification temperature is preferably room temperature, and the time is preferably 24-48 hours, more preferably 36 hours.
[0035] In this invention, the multilayer modified polybenzimidazole layer with gradient ion concentrations includes a single ion concentration gradient composite and two ion concentration gradient composites. The single ion concentration gradient composite is stacked with multiple acid-modified polybenzimidazole layers arranged from high to low hydrogen ion concentration. The two ion concentration gradient composites are stacked with acid-modified polybenzimidazole layers and alkali-modified polybenzimidazole layers arranged from high to low hydrogen ion concentration and from low to high hydroxide ion concentration. In this invention, for multiple polybenzimidazole films of different concentrations, the acid-modified films are arranged from top to bottom from high to low concentration, and the alkali-modified films are arranged from top to bottom from low to high concentration, ensuring that the peak hydrogen ion concentration and the peak hydroxide ion concentration are at the top and bottom, respectively.
[0036] In this invention, the configuration design diagrams of the single ion concentration gradient composite material and the two ion concentration gradient composite materials are as follows: Figure 1 As shown, Figure 1 In the image, (a) represents a composite material with a single ion concentration gradient, and (b) represents a composite material with two ion concentration gradients.
[0037] This invention involves hot-pressing a multilayer modified polybenzimidazole layer with a gradient ion concentration to obtain a hot-pressed material. In this invention, the hot pressing is preferably performed in a hot press, the hot pressing temperature is preferably 150-200°C, more preferably 160-180°C, the pressure is preferably 1-10 MPa, more preferably 4-8 MPa, and the holding time is preferably 10-100 min, more preferably 40-80 min.
[0038] This invention involves processing a porous hydrophilic graphene electrode on one side of the hot-pressed material with a high hydrogen ion concentration, and setting a counter electrode on the other side to obtain a humidity-self-powered device. In this invention, the preparation method of the porous hydrophilic graphene electrode preferably includes the following steps: A porous hydrophilic graphene electrode is obtained by laser irradiation on the surface of the hot-pressed material.
[0039] In this invention, the parameters of the laser irradiation include: the laser is a carbon dioxide laser, the wavelength is 10.6 μm, and the wavenumber is 900~1500 cm⁻¹. -1 The irradiation power is 0.5~10W, the laser irradiation scanning speed is 1~12 inches / s, the laser irradiation image density is 200~1000 PPI, and the defocusing degree is 0~2cm. This invention utilizes laser irradiation of acid-modified polybenzimidazole materials. The acidic molecules embedded in the polymer chain absorb laser energy to generate free radicals, causing carbon atom rearrangement on the surface and inside of the polybenzimidazole polymer material, resulting in porous hydrophilic graphene material.
[0040] In this invention, the method for setting the counter electrode preferably includes the following steps: When the counter electrode is a graphene electrode, the other side of the hot-pressed material is irradiated with a laser to obtain porous graphene as the counter electrode. In this invention, the parameters for the laser irradiation are the same as described above and will not be repeated here.
[0041] When the counter electrode is a carbon nanomaterial electrode or a metal electrode, the counter electrode and a multilayer modified polybenzimidazole layer with a gradient ion concentration are simultaneously hot-pressed.
[0042] In this invention, the fabrication process of the self-powered humidity control component is as follows: Figure 2 As shown.
[0043] This invention provides the application of the aforementioned humidity-self-powered component in humidity-based power generation. In this invention, the relative humidity (RH) of the environment is preferably 0 < RH ≤ 100%, specifically 5%, 10%, 20%, 30%, 50%, 80%, or 100%.
[0044] The following detailed description of the humidity-controlled self-powered components and their preparation method provided by the present invention, with reference to specific embodiments, should not be construed as limiting the scope of protection of the present invention.
[0045] Example 1 A self-powered component based on a single ion concentration gradient humidity is prepared using the following steps: Two polybenzimidazole films with thicknesses of 80 μm and 20 μm were selected and impregnated with different concentrations of acid. The 80 μm thick polybenzimidazole film was immersed in an 85 wt% saturated phosphoric acid solution, while the 20 μm thick polybenzimidazole film was immersed in a 10 wt% phosphoric acid solution. After immersing the films in the acid-modified solutions for two days, they were removed, cut into 2 cm × 2 cm pieces, and the thicker film was stacked on top of the thinner film. The two arranged films were then placed in a hot press for hot pressing at 150℃, 2 MPa, and 60 min, resulting in a hydrogen ion gradient composite with a decreasing concentration from top to bottom.
[0046] A laser irradiates the upper and lower surfaces of the hydrogen ion concentration composite material, thereby fabricating porous hydrophilic graphene electrodes (200 μm thick, surface roughness ≤4 μm) and reverse graphene counter electrodes (200 μm thick, surface roughness ≤4 μm) on the two surfaces of the hydrogen ion gradient concentration composite material. The laser irradiation parameters include: a carbon dioxide laser, a wavelength of 10.6 μm, and a wavenumber of 1100 cm⁻¹. -1 The irradiation power was 3W, the laser irradiation scanning speed was 10 inch / s, the laser irradiation image density was 400 PPI, the defocus degree was 1cm, and the image was selected as a 1cm linear array with a 0.2 mm gap.
[0047] Example 2 The difference from Example 1 is that the phosphoric acid solution in which the 20 μm thick polybenzimidazole film was soaked was 30 wt%.
[0048] Example 3 The difference from Example 1 is that the phosphoric acid solution in which the 20 μm thick polybenzimidazole film was soaked was 50 wt%.
[0049] Test Example 1 A passive multimeter was connected to the humidity-controlled self-powered components obtained in Examples 1-3 via an external circuit to test the real-time discharge data of the components, including the output voltage V, current I, and power generation W. The electrical performance tests of the humidity-controlled self-powered components included peak voltage, peak current, average voltage (average value of multiple self-powered tests), and average current (average value of multiple self-powered tests). Furthermore, using the peak voltage and peak current, as well as the average voltage and average current, the maximum power generation density W of the self-powered components was calculated using Equations 1 and 2. 峰值 and average power generation density W 平均 : W 峰值 =I 峰值 ×V峰值 Formula 1; W 平均 =I 平均 ×V 平均 Formula 2.
[0050] Peak voltage of self-powered humidity components under different concentration gradients, such as Figure 3 As shown, by Figure 3 It can be seen that the hydrogen ion gradient concentration composite formed by the polybenzimidazole membrane treated with 10 wt% and 85 wt% phosphoric acid solution produced a voltage performance of 0.34077 V, which is greater than the voltage performance of 0.31496 V produced by the hydrogen ion gradient concentration composite treated with 50 wt% phosphoric acid solution under the same conditions.
[0051] Peak current of self-powered humidity components under different concentration gradients, such as Figure 4 As shown, by Figure 4 It can be seen that the hydrogen ion gradient concentration composite formed by treating polybenzimidazole films with 10 wt% and 85 wt% phosphoric acid solutions produced 1186.431 μA cm⁻¹. -2 The current performance is greater than that of the composite material treated with a 50 wt% phosphoric acid solution at a hydrogen ion gradient concentration of 89.35842 μA cm⁻¹ under the same conditions. -2 Current performance.
[0052] The average voltage and average current of self-powered humidity components under different concentration gradients are as follows: Figure 5 As shown, by Figure 5 It can be seen that the hydrogen ion gradient concentration composites formed by polybenzimidazole membranes treated with 10 wt%, 30 wt%, and 50 wt% phosphoric acid solutions produced average voltage performances of 0.32733±0.01901 V, 0.24382±0.10062 V, and 0.2227±0.01491 V, respectively, and an average voltage performance of 1004.2867±257.59094 μA cm⁻¹. -2 392.1356±145.62836μA cm -2 and 91.13353±84.65096μA cm -2 The average current performance demonstrates the high level of electrical performance of composites with a large concentration gradient of hydrogen ions.
[0053] The power change of the humidity-controlled self-powered component under varying load conditions obtained in Example 1 is as follows: Figure 6 As shown, by Figure 6It can be seen that the hydrogen ion gradient concentration composite formed by treating polybenzimidazole films with 10 wt% and 85 wt% phosphoric acid solutions can generate 45 μW / cm² under a load resistance of 1000 Ω. -2 The electrical power can be used to power electronic devices with a resistance of kiloohms after multiple series and parallel connections.
[0054] Example 4 The fabrication method for a self-powered component with multi-ion concentration gradient humidity is as follows: Two polybenzimidazole films with thicknesses of 80 μm and 20 μm were selected and modified by impregnation with phosphoric acid and potassium hydroxide, respectively. The 80 μm thick polybenzimidazole film was immersed in an 85 wt% saturated phosphoric acid solution, while the 20 μm thick polybenzimidazole film was immersed in a 2 mol / L potassium hydroxide solution. After immersion in the modification solutions for two days, the films were removed, cut into 2 cm × 2 cm pieces, and the acid-modified film was stacked on top of the alkali-modified film. The two films were then placed in a hot press for hot pressing. Before hot pressing, a 200 μm thick nickel electrode was placed at the bottom of the alkali-modified film as a counter electrode. The hot pressing temperature was 200℃, the pressure was 8 MPa, and the time was 30 min, resulting in a multi-ion concentration gradient composite material.
[0055] The surface of the acid-modified film of the multi-ion concentration gradient composite was irradiated with a laser, and a porous hydrophilic graphene electrode (thickness 200 μm, surface roughness ≤4 μm) was fabricated on the surface of the acid-modified film. The laser irradiation parameters included: a carbon dioxide laser, a wavelength of 10.6 μm, and a wavenumber of 1100 cm⁻¹. -1 The irradiation power is 5W, the laser irradiation scanning speed is 5 inches / s, the laser irradiation image density is 400 PPI, and the defocusing degree is 0 cm.
[0056] Example 5 The difference from Example 4 is that the potassium hydroxide solution in which the 20 μm thick polybenzimidazole film was immersed was 4 mol / L.
[0057] Example 6 The difference from Example 4 is that the potassium hydroxide solution in which the 20 μm thick polybenzimidazole film was immersed was 6 mol / L.
[0058] Example 7 Compared to Example 4, no nickel electrode was placed at the bottom of the alkali-modified film material before hot pressing. After obtaining the multi-ion concentration gradient composite, the acid-modified film surface and the alkali-modified film surface of the multi-ion concentration gradient composite were respectively laser-irradiated. A porous hydrophilic graphene electrode (thickness of 200 μm, surface roughness ≤4 μm) was processed on the acid-modified film surface, and a graphene counter electrode (thickness of 200 μm, surface roughness ≤4 μm) was processed on the alkali-modified film surface. The laser irradiation conditions were the same as in Example 4.
[0059] Test Example 2 Referring to the test method in Test Example 1, the real-time discharge data of the humidity-self-powered components obtained in Examples 4-6 were tested. The average voltage and average current of the humidity-self-powered components under different concentration gradients are shown below. Figure 7 As shown, by Figure 7 It can be seen that the hydrogen ion-hydroxyl ion gradient concentration composites formed by treating polybenzimidazole membranes with 2 mol / L, 4 mol / L, and 6 mol / L potassium hydroxide produced average voltage performances of 0.30240±0.04138 V, 0.21638±0.02202 V, and 0.19488±0.02984 V, respectively, and an average voltage performance of 262.6892±126.13286 μA cm⁻¹. -2 21.34061±13.52698μA cm -2 and 3.13171±2.93232μA cm -2 The average current performance demonstrates the high level of electrical performance of composites with a low hydroxide ion concentration gradient.
[0060] The performance comparison results of different counter electrodes in Examples 4 and 7 are as follows: Figure 8 As shown, by Figure 8 It can be seen that the nickel electrode in the electrode assembly has different voltage and current performance compared to the laser-processed graphene electrode (LIG electrode). The preferred nickel electrode achieves a stable voltage performance of 0.312 V, which is higher than the 0.030 V voltage performance of the laser-processed graphene electrode; the preferred nickel electrode can achieve 1100 μA cm⁻¹. -2 The peak current performance mentioned above is higher than that of laser-processed graphene (0.005 μA / cm). -2 The peak current performance demonstrates the performance advantages of nickel electrodes as counter electrodes.
[0061] Example 8 Following the method described in Example 1, 12 self-powered components with a single ion concentration gradient humidity were prepared. Figure 9 A 12-unit series-connected two-dimensional planar power-generating film was obtained by connecting the units in series. The long-term supply voltage of the resulting 12-unit series-connected device is shown below. Figure 10 As shown. By Figure 10 It can be seen that as the voltage of the series device increases, its initial voltage can reach more than 2.5 V, and it can achieve a series voltage output of no less than 1.5 V during a continuous discharge process of up to ten days.
[0062] Example 9 Three polybenzimidazole films with thicknesses of 80 μm, 20 μm, and 10 μm were selected and modified by impregnation with phosphoric acid and potassium hydroxide, respectively. The 80 μm thick polybenzimidazole film was immersed in an 85 wt% saturated phosphoric acid solution, the 20 μm thick film was immersed in a 10 mol / L potassium hydroxide solution, and the 10 μm thick film was immersed in a 2 mol / L potassium hydroxide solution. After immersion in the modification solutions for two days, the films were removed, cut into 2 cm × 2 cm pieces, and stacked sequentially in the order of modification with 85 wt% saturated phosphoric acid solution, 2 mol / L potassium hydroxide solution, and 10 mol / L potassium hydroxide solution. The three films were then placed in a hot press for hot pressing at 200℃, 8 MPa, and 30 min to obtain a multi-ion concentration gradient composite.
[0063] The upper and lower surfaces of the multi-ion concentration gradient composite material are irradiated with a laser, and porous hydrophilic graphene electrodes (200 μm thick, surface roughness ≤4 μm) and reverse graphene counter electrodes (200 μm thick, surface roughness ≤4 μm) are fabricated on the two surfaces of the composite material. The laser irradiation parameters include: a carbon dioxide laser, a wavelength of 10.6 μm, and a wavenumber of 1100 cm⁻¹. -1 The irradiation power is 5W, the laser irradiation scanning speed is 5 inches / s, the laser irradiation image density is 400 PPI, and the defocusing degree is 0 cm.
[0064] Test Example 3 A single humidity-controlled self-powered component was developed using any of the methods described in Example 1. Standardized, differentiated humidity environments were constructed using a standard humidity-saturated solution, with RH values of 1%, 34%, 45%, 74%, and 95%. The self-powered component was placed in these different humidity environments, and the electrical signals within each environment were monitored. The humidity monitoring results of the humidity-controlled self-powered component are as follows: Figure 11 As shown. By Figure 11 It can be seen that, regardless of whether it is a voltage signal or a current signal, the humidity self-powered component can provide a self-powered effect with a certain degree of signal differentiation. This effect can be used to debug humidity power generation performance and also in the humidity monitoring process.
[0065] Comparative Example 1 Table 1 shows the comparison results of the electrical performance of moisture / humidity self-powered components made of different materials and the corresponding literature information: Table 1. Comparison of electrical properties of moisture / humidity self-powered components made of different materials
[0066] As shown in Table 1, the humidity-self-powered component of this invention exhibits significantly higher performance in terms of current and power than other humidity / humidity-self-powered components. The humidity-self-powered component provided by this invention can achieve self-generation under humidity conditions ranging from 0% to 95%, and is not limited to humidity levels, enabling humidity-based power generation across the entire humidity range. This performance capability is not found in other humidity-self-powered components, expanding its application scenarios under varying humidity conditions.
[0067] Comparative Example 2 Two polybenzimidazole membrane materials with thicknesses of 80 μm and 20 μm were selected and impregnated with different concentrations of acid. The 80 μm thick polybenzimidazole membrane was immersed in an 85 wt% saturated phosphoric acid solution, while the 20 μm thick polybenzimidazole membrane was immersed in 10 wt% (experimental group) and 85 wt% (control group) phosphoric acid solutions. Since both membranes were at 85 wt%, there was no concentration gradient. After immersing the membranes in the acid-modified solution for two days, they were removed, cut into 2 cm × 2 cm pieces, and the thicker membrane was stacked on top of the thinner membrane.
[0068] The counter electrode (nickel electrode) is placed at the bottom of the two pre-arranged films, and then placed in a hot press. After the hot pressing process is completed, a hydrophilic LIG electrode is prepared by laser processing of the acid-modified polybenzimidazole surface, thus completing the processing of the moisture-powered self-powered component (see Example 1 for the conditions of hot pressing and laser processing).
[0069] Voltage and current performance of 85 wt% and 10 wt% gradient composite materials without gradient composite materials as follows: Figure 12 As shown, by Figure 12 It can be seen that the electrical properties are significantly lower when gradient composite materials are not used compared to when gradient composite materials are used.
[0070] Comparative Example 3 (1) Two polybenzimidazole film materials with thicknesses of 80 μm and 20 μm were selected and impregnated with different concentrations of acid. The 80 μm thick polybenzimidazole film was immersed in 85 wt% saturated phosphoric acid solution, and the 20 μm thick polybenzimidazole film was immersed in 10 wt% phosphoric acid solution. After immersing the films in the acid-modified solution for two days, they were removed, and multiple individual films were cut into 2 cm × 2 cm pieces, with the thicker film stacked on top of the thinner film.
[0071] (2) Electrode assembly comparison: The experimental group placed the counter electrode (nickel electrode) at the bottom of the two pre-arranged membranes and then put it into a hot press. After the hot pressing process was completed, the hydrophilic LIG electrode was prepared by laser processing of the acid-modified polybenzimidazole surface (see Example 1 for the conditions of hot pressing and laser processing), thus completing the processing of the humidity self-powered component.
[0072] In the control group, the counter electrode is placed at the bottom of the two pre-arranged membranes. Before placing it into the hot press, the hydrophobic LIG electrode needs to be installed. The hydrophobic LIG electrode is a laser-induced PBI hydrophobic electrode (prepared according to patent CN202310019307.5, with a hydrophobic angle of 120°). After hot pressing, the humidity self-powered component is fabricated.
[0073] The performance comparison results of the hygroscopic electrode and the unmodified hydrophobic electrode are as follows: Figure 13 As shown, by Figure 13 It can be seen that the performance of the unmodified PBI hydrophobic electrode is significantly lower than that of the hydrophilic electrode.
[0074] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A humidity-controlled self-powered component, characterized in that, It includes a multilayer modified polybenzimidazole layer with gradient ion concentration, a porous hydrophilic graphene electrode located on one side of the multilayer modified polybenzimidazole layer, and a counter electrode located on the other side of the multilayer modified polybenzimidazole layer. The modified polybenzimidazole includes acid-modified polybenzimidazole, or includes both acid-modified and alkali-modified polybenzimidazole. When it is acid-modified polybenzimidazole, the ion is a hydrogen ion; when it is alkali-modified polybenzimidazole, the ion is a hydroxide ion. The porous hydrophilic graphene electrode is disposed on one side of the acid-modified polybenzimidazole layer.
2. The humidity-self-powered component according to claim 1, characterized in that, The multilayer modified polybenzimidazole layer with gradient ion concentration includes a multilayer modified polybenzimidazole layer with a single ion concentration gradient or a multilayer modified polybenzimidazole layer with two ion concentration gradients. The multilayer modified polybenzimidazole layer with a single ion concentration gradient is a multilayer acid-modified polybenzimidazole layer stacked together, in which the hydrogen ion concentration decreases sequentially from top to bottom; the porous hydrophilic graphene electrode is disposed on the side with high hydrogen ion concentration. The multilayer modified polybenzimidazole layer with two ion concentration gradients includes an acid-modified polybenzimidazole layer at the top and an alkali-modified polybenzimidazole layer at the bottom. The acid-modified polybenzimidazole layer has one or more layers, and when it has multiple layers, the hydrogen ion concentration decreases from top to bottom. The alkali-modified polybenzimidazole layer has one or more layers, and when it has multiple layers, the hydroxide ion concentration increases from top to bottom.
3. The humidity-self-powered component according to claim 1 or 2, characterized in that, The thickness of the single-layer modified polybenzimidazole layer is independently selected from 5 to 100 μm; The number of layers in the multilayer modified polybenzimidazole layer is 2 to 10.
4. The humidity-self-powered component according to claim 1 or 2, characterized in that, The thickness of the porous hydrophilic graphene electrode is 50~1000 μm; The counter electrode includes one of graphene electrode, carbon nanomaterial electrode and metal electrode, and the thickness of the counter electrode is 50~1000 μm.
5. The humidity-self-powered component according to claim 1 or 2, characterized in that, The humidity self-powered components can be used individually or in series or parallel.
6. The method for preparing the humidity-self-powered component according to any one of claims 1 to 5, characterized in that, Includes the following steps: Multiple modified polybenzimidazole membranes with different ion concentrations are provided. Multiple acid-modified polybenzimidazole layers are stacked in order of hydrogen ion concentration from high to low, or acid-modified polybenzimidazole layers and alkali-modified polybenzimidazole layers are stacked in order of hydrogen ion concentration from high to low and hydroxide ion concentration from low to high, to obtain a multilayer modified polybenzimidazole layer with gradient ion concentration. The multilayer modified polybenzimidazole layer with gradient ion concentration is hot-pressed to obtain a hot-pressed material; A porous hydrophilic graphene electrode is fabricated on one side of the hot-pressed material with a high hydrogen ion concentration, and a counter electrode is set on the other side to obtain a humidity-self-powered component.
7. The preparation method according to claim 6, characterized in that, Preparation methods of modified polybenzimidazole membranes with different ion concentrations Includes the following steps: Multiple polybenzimidazole membranes were immersed in acidic or alkaline solutions of different concentrations to perform acid modification or alkali modification, resulting in modified polybenzimidazole membranes with different ion concentrations. The acidic solution includes phosphoric acid solution, sulfuric acid solution, nitric acid solution or hydrochloric acid solution; The alkaline solution includes sodium hydroxide solution and / or potassium hydroxide solution; The concentration of the acidic or alkaline solution is selected from 0 to 100% saturation concentration, and the acid modification or alkaline modification time is independently 24 to 48 hours.
8. The preparation method according to claim 6, characterized in that, The method for preparing the porous hydrophilic graphene electrode includes the following steps: A porous hydrophilic graphene electrode is obtained on the surface of the hot-pressed material by laser irradiation. The parameters for the laser irradiation include: the laser is a carbon dioxide laser, the wavelength is 10.6 μm, and the wavenumber is 900~1500 cm⁻¹. -1 The irradiation power is 0.5~10W, the laser irradiation scanning speed is 1~12 inch / s, the laser irradiation image density is 200~1000 PPI, and the defocusing degree is 0~2cm.
9. The preparation method according to claim 6, characterized in that, The method for setting the counter electrode includes the following steps: When the counter electrode is a porous hydrophilic graphene electrode, the other side of the hot-pressed material is irradiated with a laser to obtain porous hydrophilic graphene as the counter electrode. When the counter electrode is a carbon nanomaterial electrode or a metal electrode, the counter electrode and a multilayer modified polybenzimidazole layer with a gradient ion concentration are simultaneously hot-pressed.
10. The application of the humidity self-powered device according to any one of claims 1 to 5 or the humidity self-powered device prepared by the preparation method according to any one of claims 6 to 9 in humidity power generation.
Citation Information
Patent Citations
A carbon-based electrode humidity sensing device, its fabrication method, carbon-based electrode humidity sensor, and its application.
CN116087281B